PENGARUSUTAMAAN GENDER DI SEKOLAH MENENGAH ATAS: KEBIJAKAN SEKOLAH DALAM MENUMBUHKAN KESADARAN GENDER DAN KEMITRASEJAJARAN LAKI-LAKI DAN PEREMPUAN Oksiana Jatiningsih dan Listyaningsih Fakultas Ilmu Sosial Universitas Negeri Surabaya (Lentera, Jurnal Studi Perempuan, 2013)
Abstract The aim of this research is to describe (1) School policy of gender education to expand the awareness of gender equality. (2) the alternatives of school policies in the practice of gender education. The research take place in SMA 15 and SMA 18. The subjects of the research are the headmaster, vice principal, counseling teachers, and students. The data collection is done by using several techniques such as Focus Group Discussion, documentation and questionnaire. The finding of the research are (1) the school is waiting the precise operational policy about PUG. (2) gender education become a part of counseling programs in a school. In terms of that, a book entitled “Building a Gender Equality and Personal Androgenus” was made. Keywords: counseling programs, gender, androgenus